Effect of different landing actions on knee joint biomechanics of female college athletes: Based on opensim simulation - Chen, Liang; Jiang, Ziang; Yang, Chen; Cheng, Rongshan; Zheng, Size; Qian, Jingguang (Frontiers in Bioengineering and Biotechnology, 2022)
[ABSTRACT] Objective: To explore the differences of anterior cruciate ligament (ACL) forces and biomechanical effects of the knee joint under three landing movements frequently used in sports training in female college athletes: drop landing (DL), drop vertical jump (DVJ) and forward vertical jump (FVJ). Methods: Eleven basketball and volleyball female college athletes (Division II and I) were recruited. Landing actions of DL, DVJ and FVJ, kinematics and dynamics data were collected synchronously using a motion capture system. OpenSim was used to calculate the ACL forces, knee joint angle and moment, and muscle forces. Data were analyzed using one-way ANOVA test. Results: At initial Contact, different landing movements influenced knee flexion angle; DL action was significantly less than FVJ action (p=0.046). Different landing actions affected quadriceps femoris forces; FVJ was significantly greater than DL and DVJ actions (p=0.002 and p=0.037, respectively). However, different landing movements had no significant effects on other variables (knee extension moment, knee valgus angle and moment, hamstring and gastrocnemius muscle forces, and ACL forces) (p > 0.050). Conclusion: The DL action had a significantly smaller knee flexion angle, which may increase the risk of ACL damage, and not recommended to assess the risk of ACL injuries. The FVJ action had a larger knee flexion angle and a higher quadriceps femoris forces that was more in line with daily training and competition needs. Therefore, it is recommended to use FVJ action in future studies on risk assessment of ACL injuries and injury prevention in female college athletes.